The use of the Er:YAG 2940nm laser associated with amorolfine lacquer in the treatment of onychomycosis - Orlando Oliveira de Morais; Izelda Maria Carvalho Costa; Ciro Martins Gomes; Dayane Higa Shinzato; Guilherme Marreta Cavalcanti Ayres; Rayane Marques Cardoso (Sociedade Brasileira de Dermatologia, 2013)
Onychomycosis is a common disease, accounting for up to 50% of all ungual pathologies. We have been developing a clinical trial (ClinicalTrials.gov: NCT01528813) using a 2940nm Er:YAG laser to fractionally ablate human nails in vivo, aiming to increase topical amorolfine lacquer delivery to the nail unit, increasing the efficacy of topical treatment of distal and lateral subungual onychomycosis. Partial results have shown an increase in areas of nail plate free of disease. We believe that ablative lasers can increase the efficacy of topical onychomycosis treatment.